Analysis of Critical Thinking Path of College Students Under STEAM Course - Sha, Jingrong; Shu, Hong; Kan, Zhaocao (Frontiers in Psychology, 2021)
This study examined the differences in critical thinking levels among students with different levels of academic engagement in STEAM courses.In this study, 30 college students were selected as subjects. Before the experiment, they received the academic engagement test and were divided into high, medium and low groups according to their performance.After that, each group received three STEAM sessions and was asked to complete a topic discussion task.The results show that there are significant differences in the critical thinking level of students with different levels of academic engagement. Specifically,The students had the medium level of academic engagement had the highest critical thinking. Research has shown that the level of academic engagement affects students' critical thinking in STEAM courses.